HUBUNGAN SANITASI DASAR DAN PERSONAL HYGIENE DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS TASIKMADU KABUPATEN KARANGANYAR - Andrean Dikky Pradhana Putra; Mursid Rahardjo; Tri Joko (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Diarrhea is a disease that can occur in infants, children and adults. The incidence of diarrhea in Karanganyar in 2015 at Tasikmadu Public Health Services amounting to 1275 cases. The purpose of this study is to identify and analyze the relationship basic sanitary conditions and personal hygiene with the incidence of diarrhea in Tasikmadu Public Health Services. This type of research used in this research is an analytic observational case control study design. Population is the case toddler who otherwise suffering from diarrhea and the control population is under five who are not otherwise suffer diarrhea. Analyzed using univariate and bivariate. The bivariate analysis using Chi Square Test (α = 0.05). The analysis showed six independent variables associated with the incidence of diarrhea in infants. Variables of clean water (ρ = 0.018 OR = 3.232 95% CI = 1294-8074), the condition of the building latrines (ρ = 0.025 OR = 3,229 95% CI = 1236-8438), the quality of garbage disposal facilities (ρ = 0.019 OR = 2,547 95% CI = 1228-5282), the quality of wastewater disposal (ρ = 0,009 OR = 2,968 95% CI = 1375-6404), personal hygiene (ρ = 0.000 OR = 6287 95% CI = 2851-13863), knowledge of the respondent (ρ = 0.040 OR = 2,981 95% CI = 1134-7831). It can be concluded that the incidence of diarrhea in Tasikmadu Public Health Services influenced by means of clean water, latrine building condition, quality means waste removal, quality of sewage disposal facilities, personal hygiene, and knowledge of parents of toddlers.